2017
DOI: 10.1002/biof.1376
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium‐induced toxicity is rescued by curcumin: A review

Abstract: Cadmium (Cd) is one of the most common environmental and occupational heavy metals with extended distribution. Exposure to Cd may be associated with several deleterious consequences on the liver, bones, kidneys, lungs, testes, brain, immunological, and cardiovascular systems. Overproduction of reactive oxygen species (ROS) as the main mechanism behind its toxicity causes oxidative stress and subsequent damages to lipids, proteins, and DNA. Therefore, antioxidants along with chelating agents have shown promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 223 publications
(268 reference statements)
3
32
0
1
Order By: Relevance
“…By contrast, the predominant responsive pathway for CdCl 2 , PFOA, TBBPA and tBHQ is the Nrf2/StRE signalling as there was no observable or insignificant induction of reporter activity in the pGL4.38‐ Cyp2a5_ StREMut cells. These observations align with the current understanding of the mechanism of action of these chemicals .…”
Section: Resultssupporting
confidence: 86%
“…By contrast, the predominant responsive pathway for CdCl 2 , PFOA, TBBPA and tBHQ is the Nrf2/StRE signalling as there was no observable or insignificant induction of reporter activity in the pGL4.38‐ Cyp2a5_ StREMut cells. These observations align with the current understanding of the mechanism of action of these chemicals .…”
Section: Resultssupporting
confidence: 86%
“…The heavy metal cadmium (Cd 2+ ) is extensively found in food materials due to its industrial use. Environmental and occupational exposure to Cd 2+ may be an important risk factor for a broad spectrum of illnesses affecting body organs such as the liver, kidneys, and cardiovascular systems [27]. Growing evidence suggests that oxidative stress induced by Cd 2+ alters the free radical-scavenging effects of N -acetyl cysteine, resulting in cellular damage via increasing genome mutations and recombination, and accelerating lipid peroxidation [23].…”
Section: Resultsmentioning
confidence: 99%
“…Upon Cd inhalation, the lungs are the main affected target and develop lung tumors, pulmonary fibrosis and emphysema. Some studies performed in animal models showed that, in response to acute exposition of rats to Cd salts, the evoked inflammatory process may induce a dose-related increase in lung LPO as measured by total lung TBARS levels [96].…”
Section: And Lipid Peroxidationmentioning
confidence: 99%